Internet Use and Psychological Wellbeing: A Study of International Students in Singapore - Dutta, Oindrila; Chye, Stefanie Yen Leng (Journal of International Students, 2018)
We investigated the relationship between psychological wellbeing (as indicated by participants’ level of loneliness, perceived academic stress and depression) and generalized problematic internet use. Data was collected from a sample of 103 international students studying in Singapore. Statistical analyses revealed that depression was the most important predictor of problematic internet use, followed by academic stress. Loneliness was found to mediate the relationship between problematic internet use and depression or academic stress. Implications of the findings for international students in the University context have been discussed.